The Effect of Self-Esteem on Mobile Phone Addiction Among College Students: Sequential Mediating Effects of Online Upward Social Comparison and Social Anxiety - Zhang P; Wang M; Ding L; Liu J; Yuan Y; Zhang J; Feng S; Liu Y (Psychology Research and Behavior Management)
Peng Zhang,1 Mingliang Wang,1 Lin Ding,1 Jinyang Liu,2 Yuqing Yuan,1 Jianing Zhang,1 Shuyuan Feng,1 Yu Liu3 1Faculty of Psychology, Tianjin Normal University, Tianjin, 300387, People’s Republic of China; 2College of Arts and Sciences, Indiana University Bloomington, Bloomington, IN, 47405, USA; 3Department of Psychology, Zhejiang Normal University, Jinhua, 321004, People’s Republic of ChinaCorrespondence: Peng Zhang, Faculty of Psychology, Tianjin Normal University, Tianjin, 300387, People’s Republic of China, Email psyzhangpeng@163.comPurpose: Mobile phone addiction threatens individuals’ physiological, psychological, and social functions, particularly among college students. While existing theories suggest a strong link between self-esteem and mobile phone addiction, the underlying mechanism remains unclear. This study aims to examine the relationship between self-esteem and mobile phone addiction in Chinese college students, exploring the chain mediation effects of online upward social comparison and social anxiety.Participants and Methods: A cross-sectional study was conducted using an offline questionnaire survey with 789 Chinese college students, employing convenience sampling in Shaanxi Province, China. Four validated instruments were employed: Self-Esteem Scale, Mobile Phone Addiction Index, Online Upward Social Comparison Scale, and Social Anxiety Scale. Descriptive analysis, correlation analysis, and mediation testing were performed to analyze the data.Results: The results showed that self-esteem influences mobile phone addiction through three pathways: (1) self-esteem → online upward social comparison → mobile phone addiction, with a 95% confidence interval of [− 0.048, − 0.010], indicating a significant mediation effect (effect value = − 0.027, accounting for 14.86% of the total effect); (2) self-esteem → social anxiety → mobile phone addiction, with a 95% confidence interval of [− 0.182, − 0.106], indicating a significant mediation effect (effect value = − 0.143, accounting for 78.57% of the total effect); (3) self-esteem → online upward social comparison → social anxiety → mobile phone addiction, with a 95% confidence interval of [− 0.016, − 0.003], suggesting a significant mediation effect (effect value = − 0.009, accounting for 4.95% of the total effect).Conclusion: These findings indicate that online upward social comparison and social anxiety serially mediate the relationship between self-esteem and mobile phone addiction. The study reveals how self-esteem contributes to mobile phone addiction among college students and provides insights for prevention and intervention strategies.Keywords: self-esteem, online upward social comparison, social anxiety, mobile phone addiction, college students